2020
DOI: 10.1021/acsami.9b20794
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous Hydrogel Scaffolds with Tunable Physicochemical Properties for Tissue Engineering Constructed Using Renewable Polysaccharides

Abstract: Polysaccharides have recently attracted increasing attention in the construction of hydrogel devices for biomedical applications. However, polysaccharide-based hydrogels are not suitable for most preclinical applications because of their limited mechanical properties and poor tunability. In this study, we employed a simple and eco-friendly approach to producing a macroporous polysaccharide hydrogel composed of salecan and κ-carrageenan without the use of toxic chemicals. We evaluated the physicochemical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 42 publications
(65 reference statements)
4
32
0
Order By: Relevance
“…3 E, more typical F-actin fibers appeared in the cells adhered to APG3 compared with cells adhered to AHG. It was reported that integrins governed the cell adhesion, and increasing integrin aggregation promoted the formation of F-actin fibers [ 10 , 28 , 51 ]. As expected, cells cultured on APG3 displayed prominent integrin clustering, while the cells on AHG displayed low levels of integrin clustering ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 E, more typical F-actin fibers appeared in the cells adhered to APG3 compared with cells adhered to AHG. It was reported that integrins governed the cell adhesion, and increasing integrin aggregation promoted the formation of F-actin fibers [ 10 , 28 , 51 ]. As expected, cells cultured on APG3 displayed prominent integrin clustering, while the cells on AHG displayed low levels of integrin clustering ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical parameters of hydrogel scaffolds will be sensed by cells and affect the cell behavior [ [6] , [7] , [8] ]. An idea hydrogel scaffold requires to match the tissue and ECM mechanics [ 9 , 10 , 11 ]. As living tissues and ECMs exhibit complex, time/rate dependent mechanical behaviors, it is essential to construct a hydrogel platform with adjustable mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24,25 ] A series of electrochemistry‐induced reactions resulted in two kinds of molecular interactions in the hydrogel model: one was coordination interaction of Fe 3+ ions with the sulfate groups of κ‐carrageenan; the other was from the molecular hydrogel‐bonding interactions between Fe 3+ ‐coordinated κ‐carrageenan and PAAm networks. [ 26,27 ] These two molecular interactions elicited functional improvements for the composite PAAm@κ‐carrageenan hydrogel in mechanical strength, interfacial adhesion, self‐healing, and surface patterning (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogels are three-dimensional networks composed of hydrophilic polymers cross-linked through covalent bonds or held together via physical intermolecular interactions [9,10]. Over the past few decades, methods for administering drugs via hydrogels have gained increasing attention, as regulating the rate of drug release with a controlled release; the mechanism offers numerous advantages over conventional dosage regimens [11,12].…”
Section: Introductionmentioning
confidence: 99%